2011
DOI: 10.17509/ijal.v1i1.99
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPING an ENGLISH PERFORMANCE TEST for INCOMING INDONESIAN COLLEGE STUDENTS

Abstract: This study constructed, developed and validated an English Performance test designed to provide a valid criterion-based measurement within the placement programs in Indonesian universities. The steps in developing a performance test involved conducting needs analysis, establishing attributes of good performance test, and constructing test specification based on current language testing theory. The test was validated in several ways: (1) face validation, (2) content validation, (3) concurrent validation, and (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The study also answers the second research questions and the results are learning principles and the process of validation. The product of the R and D is designed to easy the user when writing iBT TOEFL essays as a solution of the previous studies [12], [13], [65]. This study was also the perpetuation of the recent studies by the researcher [16], [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also answers the second research questions and the results are learning principles and the process of validation. The product of the R and D is designed to easy the user when writing iBT TOEFL essays as a solution of the previous studies [12], [13], [65]. This study was also the perpetuation of the recent studies by the researcher [16], [66].…”
Section: Discussionmentioning
confidence: 99%
“…Sathya (2013) reported the result of his study "Developing an E-Content Module on the poem [12]. Foley reported her study on the four skills; "Developing Academic Writing", whereas Wullur [13] reported their R and D in the productive skills: "Developing an English Performance Test" [13]. All of these studies have left great potential gaps for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Criterion-referenced tests are measures that allow ascertaining task performance of a test taker with respect to a set of criteria rather than a comparison with other testees (Popham & Husek, 1969). Further, a criterion-referenced test as an authentic and productive test, is the answer to the need of language teaching and testing communicatively (Wullur, 2011). Educational tests for instructional decision making are often criterion referenced.…”
Section: Bands/levels Of Speaking Performance and Descriptorsmentioning
confidence: 99%